Understanding Socioeconomic Differences in Parents' Speech to Children. (23rd November 2017) - Rowe, Meredith L.
Abstract: In this article, I address our understanding of the word gap, or why parents' talk to children differs by socioeconomic status. The differences in quantity and quality of parents' input across early childhood predict children's language development and their readiness for school. As a result, a growing number of interventions target parent–child interactions to enhance children's early experiences and promote learning. Understanding the factors that shape parents' communication with their children is essential and has implications for empirical research as well as interventions to reduce early disparities in children's language development.